Using a Performance Measurement Framework to Overcome the Odds against Performance Management in the Public Sector - Nabaho, Lazarus (Uganda Management Institute, 2011)
The importance of measuring the efficiency and effectiveness of governmental programmes features prominently in almost every discourse related to programme monitoring and evaluation. Phrases like ‘what gets measured gets done and if you cannot measure it you cannot manage it’ attest to the signifi cance attached to measuring the effi ciency and effectiveness of governmental programmes. Despite the apparent appreciation of the benefi t of performance measurement, how to measure the performance of governmental programmes continues to elude academics and practitioners of public management. This article, informed by available literature on performance measurement in the public sector and the New Public Management paradigm, contends that measuring the effi ciency and effectiveness of governmental programmes requires development of a performance measurement framework or logical model consisting of outcomes, outputs, activities and inputs for the programme. Performance indicators, that specify what to measure, should consequently be developed for each component in the results framework. Since performance measurement hinges upon availability of timely and reliable information, identifi cation of the sources of information on performance indicators; determination of the methods and frequency of data collection; and assignment of the responsibility for data collection are stressed in discussion.
Keywords: efficiency; effectiveness; governmental programmes